Exploring terrain indices and slope morphometry for trail and campsite planning on Mount Irau, Malaysia - Sapian, M S S; Unfound, Unfound; Zawawi, A A Z; Balakrishnan, T; Ismail, M H (Department of Forest Management, 2023)
Terrain analysis and elevation profiling are widely utilized in geographical studies where spatial information system is one of the foremost tools in assessing characteristic patterns of hiking trails and plain areas suitable for a campsite. The main objective of this study is to classify the landforms of Batu Gangan Forest Reserve by conducting a morphometric analysis of the digital terrain model (DTM) with a 10 m resolution. The classification process is based on calculating the topographic position index (TPI). Using TPI, the landscape was classified into slope position and landform categories. The delivered TPI landform classes are spatially correlated with the elevation, slope, LS factor, and topographic wetness of the mountain. Site observation was carried out to identify water sources, viewpoints, and their significance as suitable campsites and potential trails. An alternative trail was proposed to reduce the visitor impacts towards the main trail. The result suggested that the plains landform only covered 3.26% or 2.03 km2 of the study area, where two potential campsites were identified. The method presented and research findings derived from the study are beneficial to support sustainable recreation resource planning, especially in a complex mountainous area. The study's findings and data will lead to proper forest use for recreational reasons consistent with conservation efforts.